Establishing cocooning apple leafcurling midge onto apples for disinfestation research - Hawthorne, A.J.; Griffin, M.J.; Page-Weir, N.E.M.; Redpath, S.P.; Jamieson, L.E. (New Zealand Plant Protection, 2016)
Apple exports intercepted with cocooning apple leafcurling midge (ALCM) are fumigated with methyl bromide (MB) which reduces apple quality ALCM is controlled in the orchard using the insecticide Movento while also being parasitised by Platygaster demades and preyed on by generalist predators such as Sejanus albisignata These ALCM control measures make it difficult to collect sufficient numbers of ALCMinfested apples for disinfestation research on alternatives to MB Therefore procedures were developed for collecting and storing cocooning ALCM on apples in the laboratory ALCMinfested leaves were collected in plastic bags saturated with water and placed at 20C The water stimulated larvae to exit the leafrolls Using a fine paint brush ten larvae were placed on the calyx of an apple and confined using a cage attached with BluTak The apples were placed in plastic bins and sprayed with water A mesh net and a brown paper bag were secured over the top of the bin to reduce condensation The bin was stored at 20C 168 lightdark for 1015 days Of 1133 apples established 988 of them (872 ) had on average 22 cocooning ACLM Large numbers of cocooning ALCM on fruit can now be provided for disinfestation research